Strengthening the Icon Management of Kampung Kopi Village in Malang of Indonesia by Improving the Quality of Production and Marketing for Farmers - Winarno, Agung; Agustina, Yuli; Narmaditya, Bagus Shandy; Wahyuni, Wiwik (Technium Social Sciences Journal, 2021)
Malang regency of East Java is well-known for its numerous agricultural crops. One of them is coffee, which is grown in Benjor Village, Tumpang District. The area is one of the coffee bean growers in the Malang Regency. Typically, farmers sell their coffee in the form of logs, unprocessed. Numerous coffee harvests are lost, and the quality of the crop is deteriorating. As a result, farmers earn a pitiful amount of money. This project aims to empower the Benjor Village, Tumpang District, Malang Regency community of coffee grower groups. The activities began with the process of identifying and executing methods for optimizing coffee yields through the use of post-harvest processing technology to improve the quality of coffee beans and hence boost the selling price. Program planning, execution, monitoring, and evaluation are the strategies employed. The findings indicate that not all groups of coffee farmers in Benjor Village, Tumpang District, Malang Regency have the knowledge and abilities necessary to research and apply technology to maximize their postharvest coffee yields. Even though this can result in a higher selling price for coffee. Therefore, the public's attention is opened to the potential for greater diversification of post-harvest coffee products.